2018
DOI: 10.22159/ijap.2018v10i6.29346
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Pcr–based Detection Optimization of Porcine Dna in Gelatin Capsule Shell

Abstract: Objective: This study was conducted to optimize the genomic deoxyribonucleic acid (DNA) based molecular detection of gelatin derived from porcine by performing polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and duplex PCR method employing cyt B gene.Methods: Optimization was carried out for DNA extraction, PCR conditions, and the sensitivity of the PCR-RFLP method. Due to the very low DNA trace in gelatin after the various manufacturing process, the extraction was optimized to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…To date, no literature regarding gelatin has been reported. Gelatin is obtained from collagen hydrolysis and undergoes harsh manufacturing steps, which could result in DNA removal or in the degradation of DNA to small fragments (Khayyira, Estepane, & Malik, 2018). Our study confirmed that gelatin DNA was damaged to various degrees at different stages of processing, especially at the decoction to concentrated gel stage, as well as when the temperature or pressure was increased or lengthened.…”
Section: Resultsmentioning
confidence: 99%
“…To date, no literature regarding gelatin has been reported. Gelatin is obtained from collagen hydrolysis and undergoes harsh manufacturing steps, which could result in DNA removal or in the degradation of DNA to small fragments (Khayyira, Estepane, & Malik, 2018). Our study confirmed that gelatin DNA was damaged to various degrees at different stages of processing, especially at the decoction to concentrated gel stage, as well as when the temperature or pressure was increased or lengthened.…”
Section: Resultsmentioning
confidence: 99%